PENGARUH KUALITAS SISTEM DAN KUALITAS INFORMASI PORTAL AKADEMIK UNIVERSITAS NEGERI PADANG TERHADAP KEPUASAN PENGGUNA - Muhammad Imam Andikha; Rahmiati Rahmiati; Thamrin Thamrin (Jurnal Ecogen, 2019)
This study aims to determine the effect of System Quality and Information Quality of UNP Academic Portal on User Satisfaction. This type of research is quantitative descriptive. This research was conducted in the University of Padang. While the research time was carried out in July-August 2018. The population in this study were UNP students who were enrolled actively in 2016 with a sample of 400 people taken by probability sampling. Data is processed using multiple linear regression using a SPSS 16.0 program. The results showed that System Quality had a significant positive effect on User Satisfaction and Information Quality had a significant positive effect on User Satisfaction at α = 0.05Keywords: Information Systems, System Quality, Information Quality, User Satisfaction